'When will I be free': Lessons from COVID-19 for Child Protection in South Africa. (December 2020) - Haffejee, Sadiyya; Levine, Diane Thembekile
Abstract: Background: COVID-19 has highlighted and amplified structural inequalities; drawing attention to issues of racism, poverty, xenophobia as well as arguably ineffective government policies and procedures. In South Africa, the pandemic and the resultant national lockdown have highlighted the shortcomings in the protection and care of children. Children in alternative care are particularly at risk as a result of disrupted and uncoordinated service delivery. Objective: The aim of this study was to explore the experiences and impact of the pandemic and the resulting social isolation on the wellbeing and protection of children living in a residential care facility. Methods and participants: We used qualitative, participatory approaches – specifically draw-and-write methods – to engage with 32 children (average age = 13.5 years) living in a residential care facility in Gauteng. Findings: Children in care demonstrated an awareness of the socio-economic difficulties facing communities in South Africa, and shared deep concerns about the safety, well-being and welfare of parents and siblings. Although they expressed frustration at the lack of contact with family members, they acknowledged the resources they had access to in a residential care facility, which enabled them to cope and which ensured their safety. Discussion and conclusion: We focus our discussion on the necessity of a systemic response to child welfare, including a coordinated approach by policy makers, government departments and child welfare systems to address the structural factors at the root of inequality and inadequate, unacceptable care. This response is essential not only during COVID-19 but also in pre- and post-pandemic context.